La langue du peuple dans la littérature (De Gruyter, 2025)
From the classical age to contemporary Francophonie, French-language literature features numerous instances of popular speech, whose mimetic or conventional character remains open to debate. This book brings together contributions from linguists and literary scholars who, through eleven case studies, explore the tension between the evocation of spontaneous orality and the elaboration of literary dialogicity.